2018
DOI: 10.1111/camh.12298
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Practice: Dialectical behaviour therapy for adolescents: multisite implementation and evaluation of a 16‐week programme in a public community mental health setting

Abstract: Background Dialectical behaviour therapy for adolescents (DBT‐A) is an intervention with a growing evidence base for treating adolescents with emotional and behavioural dysregulation. This study describes the implementation and effectiveness of 16‐week DBT‐A across multiple sites in publicly funded child/adolescent mental health services (CAMHS) in Ireland. Method The Consolidated Framework for Implementation Research was used to guide this national implementation. Fifty‐four clinicians from seven CAMHS teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Methods detailing the implementation and evaluation of DBT-A in community settings across Ireland have been described in greater detail in a separate paper (Flynn, Kells, Joyce, Corcoran et al, 2018). The main issues relevant to this comparison study are described below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods detailing the implementation and evaluation of DBT-A in community settings across Ireland have been described in greater detail in a separate paper (Flynn, Kells, Joyce, Corcoran et al, 2018). The main issues relevant to this comparison study are described below.…”
Section: Methodsmentioning
confidence: 99%
“…During the initial 2 years of the project (2013)(2014)(2015), seven CAMHS teams trained in DBT and delivered the 16-week DBT-A programme as described by Miller et al (2007). The implementation and evaluation of the 16-week DBT-A programmes delivered by these seven CAMHS teams were explored by the authors and significant improvements were observed for adolescents on all outcome measures including frequency of self-harm and suicidal ideation (Flynn, Kells, Joyce, Corcoran et al, 2018). Outcomes and experiences of parents who participated in the 16-week skills group, which is part of the multifamily group component of DBT-A, were also evaluated with reductions reported in levels of burden, grief and stress (Flynn, Gillespie, & Joyce, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Most children and adolescent patients (youth patients, hereafter) with mental disorder can be and should be managed as outpatients in the community, therefore to maximize the involvement of their families and other resources [10,11]. However, for some severe cases or those who are in acute crisis, psychiatric hospitalization remains a necessary and effective treatment option, although the duration has shortened significantly compared with what was in the past [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Most child and adolescent patients (youth patients, hereafter) with mental disorder can be and should be managed as outpatients in the community, to maximize the involvement of their families and other resources [10,11]. However, for some severe cases or for those who are in acute crisis, psychiatric hospitalization remains a necessary and effective treatment option, although the duration has shortened significantly compared with what it was in the past [12][13][14].…”
Section: Introductionmentioning
confidence: 99%